2012
DOI: 10.3389/fpls.2011.00106
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pre-Harvest Foliar Application of Citric Acid and Malic Acid on Chlorophyll Content and Post-Harvest Vase Life of Lilium cv. Brunello

Abstract: Citric acid is a regular ingredient in many vase solution formulations but pre-harvest use of citric acid is a novel method in vase life extension of cut flowers, which is reported on tuberose earlier. In order to verify previous result, and check for possible substitution of citric acid by malic acid, the current research was designed. Citric acid (0, 0.075, 0.15% w/v) and malic acid (0, 0.075, 0.15% w/v) were used in a factorial design with three replications. Foliar sprays were applied two times during grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 18 publications
5
40
0
Order By: Relevance
“…Peach fruit is typical climacteric fruit and experiences fast ripening after harvest, which makes it easily perishable and have a limited shelf life (Farooq et al, 2018). Exogenous organic acid treatment has been reported to have potential to maintain postharvest quality in fruit (Huang, Jian, Jiang, Duan, & Qu, 2016) and plays a role in regulating plant maturation and senescence (Choehom, Ketsa, & van Doorn, 2004;Darandeh & Hadavi, 2012). Citric acid, as an important organic acid in plants, can also efficiently improve postharvest fruit quality, which has been proven in studies on apple and litchi (Jiang, Fu, Zauberman, & Fuchs, 1999;Santerre, Cash, & Vannorman, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Peach fruit is typical climacteric fruit and experiences fast ripening after harvest, which makes it easily perishable and have a limited shelf life (Farooq et al, 2018). Exogenous organic acid treatment has been reported to have potential to maintain postharvest quality in fruit (Huang, Jian, Jiang, Duan, & Qu, 2016) and plays a role in regulating plant maturation and senescence (Choehom, Ketsa, & van Doorn, 2004;Darandeh & Hadavi, 2012). Citric acid, as an important organic acid in plants, can also efficiently improve postharvest fruit quality, which has been proven in studies on apple and litchi (Jiang, Fu, Zauberman, & Fuchs, 1999;Santerre, Cash, & Vannorman, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Citric acid reduced bacterial population in vase solution and increased the water conductance in xylem of cut flowers (van Doorn, 1997). Similarly, Citric acid significantly transported iron in plants (Hell & Stephan, 2003;Darandeh & Hadavi, 2012).…”
Section: Vase Life (Days)mentioning
confidence: 89%
“…The highest vase life in rose was recorded by Jowkar et al (2012) at 300 mg/lcitric acid concentration. Organic acids such as citric acid were reported as the source of carbon and energy for cells and used in the respiratory cycle and some other biochemical pathway (da Silva, 2003;Darandeh & Hadavi, 2012). Citric acid reduced bacterial population in vase solution and increased the water conductance in xylem of cut flowers (van Doorn, 1997).…”
Section: Vase Life (Days)mentioning
confidence: 99%
“…Later studies revealed that the CA effect is not just due to pH change and there are a variety of physiological responses to applied CA; foliar use of CA alone or in combinations with SA and malic acid increased the essential oil production of Basil (Jaafari and Hadavi, 2012) and Dill (Jafari and Hadavi, 2012). Some physiological parameters were improved in Tuberose by application of foliar CA (Eidyan et al, 2014), Lilium (Darandeh and Hadavi, 2012), and Bean (El-Tohamy et al, 2013). The increase in the vase life of cut rose flowers obtained in the soilless culture system by foliar pre-harvest application of the combinations of SA and CA revealed that the obtained results are not necessarily dependent on soil system (Hajreza et al, 2013).…”
Section: Introductionmentioning
confidence: 93%